Perempuan dan Politik: Analisis Kesetaraan Gender Dalam Tayangan Film Barbie Tahun 2023 Dalam Perspektif Feminisme - Pratiwi, Kartinia Indah; Angela, Deni (Jayapangus Press, 2024)
In the era of globalization and rapid media development, films as a form of popular entertainment have a significant influence in shaping society's understanding of gender equality and feminism. This research aims to analyze gender equality in Barbie films from a feminist perspective, with a focus on Indonesia's young generation, towards gender equality for women in the family and public spaces. The film was chosen as the subject of study because it has the potential to shape the views of the younger generation regarding gender issues and the feminist movement in Indonesia. In line with this aim, this research has a qualitative approach, with an explanatory type of research through case studies. For data collection techniques through primary data and secondary data. Primary data through in-depth interviews, and secondary data through library research and document studies. The theories used are The Politics of Presence by Anne Phillips and The Media of Film by Triana Robbins, Peter Coogans, Bradford W. Wright, and Will Broker, and Tolstoy. The results of this research are to provide a better understanding of variations in public perceptions of gender equality in Barbie 2023, as well as how identity politics factors, including gender identity and patriarchal culture, influence these perceptions. These findings provide in-depth insight into the role of entertainment media in shaping the attitudes and political views of Indonesia's young generation towards gender equality with a focus on gender issues, as well as assisting policy makers in designing communication strategies that are more sensitive to gender equality. The patriarchal culture in the film Barbie 2023 is still a big obstacle to gender equality. The Barbie film helps highlight this issue and invites society to give equal rights to women.